Bioaccumulation of 4-nonylphenol and effects on biomarkers, acetylcholinesterase, glutathione-S-transferase and glutathione peroxidase, in Mytilus galloprovincialis mussel gills. (May 2015) - Vidal-Liñán, Leticia; Bellas, Juan; Salgueiro-González, Noelia; Muniategui, Soledad; Beiras, Ricardo
Abstract: Wild marine mussels, Mytilus galloprovincialis showed a moderate bioaccumulation ability when exposed to waterborne 4-nonylphenol (4-NP), with a bioconcentration factor (BCF) of 6850 L Kg −1 (dry weight). Kinetic and concentration-response experiments were performed and three enzymatic biomarkers in mussel gills were measured: Glutathione S-transferase (GST), glutathione peroxidase (GPx) and acetylcholinesterase (AChE). Exposure of mussels to environmentally relevant concentrations (25–100 μg L −1 ) of 4-nonylphenol significantly inhibited the AChE activity and induced the GST and GPx activities. GST induction was dose dependent whilst GPx activity showed a less consistent pattern, but in both cases the induction remained after a 10 d depuration period. Mussels seem capable of eliminating 4-NP from their tissues through a mechanism involving GST induction. Highlights: Accumulation of 4-NP in mussels seems to be moderate compared to other organics, with a BCF = 6850 L kg −1 . GST was the biomarker that yielded the highest sensitivity to this compound. GST activity was significantly induced after 15 d exposure to 4-NP concentrations from 50 μg L −1 . GST induction was associated to a reduction in 4-NP in the mussel tissues. AChE activity was significantly inhibited after 30 d exposure at 75 μg L −1 . Abstract : The biotransformation of 4-NP in Mytilus galloprovincialis seems to involve GST, which was significantly induced in a dose:response pattern with 4-NP exposure.